Exploring future rice market segments and trait priorities in the face of climate change in Southeast Asia - Valera, Harold; Bayot, Ruvicyn; Pede, Valerien; Demont, Matty; Connor, Melanie (CGIAR System Organization, 2025)
Rice production provides food security for billions of people in Southeast Asia (SEA). However, it is negatively influenced by changing climatic conditions, such as extreme weather events and increasing temperatures. This is exacerbated by increasing marginal cropping areas (e.g., those with high salinity, poor soil quality, high soil toxicity, etc.). There is thus a need to review and explore the current seed product market segmentation and the corresponding target product profiles for potential future requirements that increase climate mitigation and adaptation potential. This brief uses the findings from the latest research on farmer requirements and future climate change scenarios to identify future market segments and important traits that enhance sustainability and resilience in SEA. We used Impact Opportunities, Market Segments, and Target Product Profile (TPP) portals hosted in the Global Market Intelligence Platform (GloMIP) to offer background information on the relevance of the SEA rice market. Climate change scenario analysis points to adverse effects on rice production in SEA. Possible strategies could focus on including agronomic traits such as water-use efficiency, nutrient-use efficiency, and shifting to short-duration varieties in the TPPs. In addition, the recent increased importance of direct-seeded rice and the shift from transplanting to direct-seeding in Thailand could create a major change in the size of some transplanted market segments in Viet Nam and Myanmar vis-à-vis direct-seeded segments. Furthermore, two potential new market segments were identified: perennial rice and rice ratooning, which could help to address climate change.